Body image and attitudes toward cosmetic surgeries among female college students in the United Arab Emirates: A cross-sectional study - Ahmad M. Al-Bashaireh; Yousef Aljawarneh; Osama Alkouri; Foad Alzoughool; Amal Alhefeiti; Amnah Aldhuhoori; Amnah Al Kaabi; Aseilah Alkaabi; Fawzia Alnaqbi (Heliyon)
Background: Due to the continuously increasing popularity of cosmetic surgeries, the influence of physical and facial beauty is pervasive worldwide. It encourages females to seek to meet specific beauty standards and not be content with their natural features. This study aimed to assess knowledge and motivation toward cosmetic surgeries, determine the prevalence of cosmetic surgeries, and examine the relationships between body image and attitude toward cosmetic surgeries among female college students. Methods: This study utilized a cross-sectional study design. Data were collected using Demographic Data Questionnaires, Cosmetic-related Questionnaire, the Body Appreciation Scale (BAS), and the Attitude Toward Cosmetic Surgery Scale (ACSS). Results: A total of 783 participants were enrolled in this study. The mean age of the participants was 20.95 years (SD = 2.149). The result showed that 47.6 % of participants considered cosmetic surgery necessary. While awareness of the potential side effects associated with cosmetic surgery varied among participants, most respondents acknowledged the existence of side effects (55.3 %). The most recognized type of cosmetic surgery among the respondents was filler (70.1 %). The primary motivation for cosmetic surgery was to enhance their appearance (67.9 %). On the other hand, the reasons for not having cosmetic surgery included high costs (49.4 %). Most participants (65.3 %) had no experience with any form of cosmetic surgery. Botox and filler were the most common types experienced by 5 % and 13.5 % of participants, respectively. Participants reported high body image scores (4.09 ± 0.95) and attitudes toward cosmetic surgeries (3.89 ± 1.42). The study found no significant correlation between body image and attitude toward the acceptance of cosmetic surgery (r = - 0.016, p < 0.697). However, a group who received cosmetic surgery was found to have a lower significant score of body image but a higher significant level for score of attitudes toward cosmetic surgery than the group who did not receive cosmetic surgeries. Conclusion: This study found that female college students showed varying levels of awareness regarding the side effects associated with cosmetic procedures. The most recognized type of cosmetic surgery among respondents was fillers, and the primary motivation for seeking such procedures was the desire to enhance appearance, while cost is the main reason for not seeking cosmetic surgeries. Furthermore, a study found those who received cosmetic surgeries reported a lower level of body image but a higher level of acceptance of cosmetic surgeries. The study emphasizes the need for future research endeavors to delve deeper into this subject matter using more robust research designs and methodologies. Moreover, a culturally tailored educational campaign is needed to enhance students' capacity for making informed decisions and instill a conscientious approach to personal health and aesthetic considerations.